JAK2 V617F Analysis in Indonesian Myeloproliferative Neoplasms Patients - Fanti Saktini; Santosa Santosa; Sultana MH Faradz (Journal of Biomedicine and Translational Research, 2015)
Background : Three subtypes of myeloproliferative neoplasms (MPNs): Polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF) showed overlapping phenotype. There has been no specific cytogenetic marker identified in these subtypes. JAK2 V617F mutation prevalence in Caucasian MPNs was first reported as 97% in PV, 57% in ET, and 50% in PMF.Objective: This study was done to define the prevalence of JAK2 V617F mutation and to identify cytogenetic markers in MPNs.Methods : The study design was cross-sectional. Patients who were admitted to Dr. Kariadi Hospital with clinical diagnosis of MPNs were referred for bone marrow cytogenetic analysis in Telogorejo Hospital. JAK2 V617F mutation was tested for using Amplification Refractory Mutation System Polymerase Chain Reaction (ARMS-PCR) from peripheral blood vein. Clinical data were secondary data retrieved from hospital medical records.Results :  There was no cytogenetic abnormality found in all MPNs patients. The prevalence of JAK2 V617F mutation in MPNs patients was 73,68%. Mutation prevalence distribution in each subtypes were 100% in PV, 63,6% in ET and 100% in PMF. Conclusion : Chromosomal abnormality was not found using conventional cytogenetic analysis. More sensitive methods might elucidate submicroscopic chromosomal abnormalities in these patients. The prevalence of JAK2 V617F mutation was comparable with studies in Caucasian. It is recommended that JAK2 V617F testing should be incorporated in the management therapy of MPNs in Indonesia.